A Study on Impact of Stress towards Work Related Behavior among Secondary School Teachers in Malawi - Palanivel, R. V.; Michael, S. (International Journal of Multidisciplinary: Applied Business and Education Research, 2020)
This investigation conducted on impact of stress towards work be-havior among secondary school teachers in Mangochi, Malawi. 200 secondary school teachers were randomly chosen to form as partici-pants for the investigation. Data were collected by using research questionnaire titled “stress management in educational sector”. The purpose of this study was to identify the various impacts of stress to-wards work related behavior among secondary school teachers. This study reported that teachers were encountered impacts on job re-lated behaviors such as losing interest in teaching, committing a lot of errors in work, Not attending to students’ needs, transferring of ag-gression to students, increasing Absence. Male teachers encountered more impacts in job related behaviors compared to female teachers. There was positive correlation between age of the respondents and respondents encountered in job behaviors. Master degree holders en-countered more job-related impacts compared to all other teachers who are all secured certificate, diploma and Bachelor degree. Teach-ers who are having experience between 11–15 and 16–20 years en-countered more stress impact on job behavior compared to teachers who are having experience in teaching between 0 to 10 years.